2022
DOI: 10.1002/smll.202107450
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Surface and Interface Structures of Copper‐Based Catalysts for Electrochemical Reduction of CO2 to Ethylene and Ethanol

Abstract: Electrochemical CO2 reduction to valuable ethylene and ethanol offers a promising strategy to lower CO2 emissions while storing renewable electricity. Cu‐based catalysts have shown the potential for CO2‐to‐ethylene/ethanol conversion, but still suffer from low activity and selectivity. Herein, the effects of surface and interface structures in Cu‐based catalysts for CO2‐to‐ethylene/ethanol production are systematically discussed. Both reactions involve three crucial steps: formation of CO intermediate, CC cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
93
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 146 publications
(353 reference statements)
0
93
0
Order By: Relevance
“…Among them, Cu-based catalysts have been reported to have excellent catalytic activity in the field of CO 2 reduction reactions. [29][30][31] Gong's group constructed oxy-derived copper catalysts with stable nanostructures and Cu/Cu + heterogeneous interfaces to achieve the efficient reduction of CO 2 to C 2 H 4 . [31] In addition, Zhou's group prepared a composite with copper nanoparticles anchored on the nitrogen-doped graphene (denote as Cu-NG) as a cathode which is applied in the Li-CO 2 battery.…”
Section: Research Articlementioning
confidence: 99%
“…Among them, Cu-based catalysts have been reported to have excellent catalytic activity in the field of CO 2 reduction reactions. [29][30][31] Gong's group constructed oxy-derived copper catalysts with stable nanostructures and Cu/Cu + heterogeneous interfaces to achieve the efficient reduction of CO 2 to C 2 H 4 . [31] In addition, Zhou's group prepared a composite with copper nanoparticles anchored on the nitrogen-doped graphene (denote as Cu-NG) as a cathode which is applied in the Li-CO 2 battery.…”
Section: Research Articlementioning
confidence: 99%
“…The electrochemical CO 2 reduction reaction (ECO 2 RR) offers a promising approach for curbing anthropogenic CO 2 emissions, storing intermittent power from solar, wind, and thermal sources, and producing value-added chemicals or fuels including carbon monoxide, formic acid, ethylene, and ethanol. Due to the thermodynamic stability of CO 2 , a rational catalyst design is required to reduce the activation energy barrier for the ECO 2 RR . Over the past decade, numerous efficient catalysts have been developed and various chemicals such as carbon monoxide, ethylene, and ethanol can be produced depending on the catalyst types. The carbon abatement capability has a strong dependence on the chemical product.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 Previous works have confirmed that the highly conductive transition metal sulfides (TMSs) with favorable H 2 O adsorption show promising potential in H 2 O splitting to replace precious metals. [23][24][25][26][27][28][29][30][31] Nevertheless, pure TMSs exhibit weak adsorption on nitrobenzene (PhNO 2 ), which leads to premature desorption of PhNO 2 on the catalyst surface, leading to insufficient and incomplete reduction to PhNH 2 . 15 To this end, interface engineering is an efficient strategy towards electronic structure regulation of interfacial active sites for designing efficient electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%